Analisis Kinerja Pegawai Melalui Komitmen Organisasional, Lingkungan Kerja dan Kepuasan Kerja Pegawai Pemerintah Kota Mataram - H. Abdul Malik (Universitas 17 Agustus 1945 Surabaya, 2015)
AbstractThe low Employee satisfaction, and followed by the low organizational commitment and work environment are less well causing the performance of civil servants is still low. The low of job satisfaction aspects obtained less satisfaction from employee’s on their allowances and compensation they received. As seen from the grant of the allowance system welfare that only based on the level of structural and the position/rank without considering the work achievement. Similarly in terms of promotion has not been refers to competency and the sequence line.The population in this research is the civil servant in Mataram City Government, the Secretariat of The Parliament, Dinas, Bappeda, Inspectorates, Regional Technical Institute Mataram in West Nusa Tenggara province, with the total number of 1.058 employees.From the test results of this research, a model with Maximum Likelihood Estimation (MLE), analysis of structural equation modeling (SEM), proportional random sampling method by software Amos 20 on 152 respondents.The results showed that: 1). Organizational Commitment has towards Employee’s job satisfaction at Government of Mataram. 2). Organizational Commitment has effect on the performance of the employees of the City Government of Mataram. 3). Work environment has influence towards employee’s job satisfaction at Government Mataram 4). Work environment has influence towards employees performance of Government of Mataram. 5). Employees job satisfaction has influence towards employees performance Government of Mataram. Key words: organizational commitment, work environment, job satisfaction, performance.